Modification method for improving strength of AZO target blank

By using matrix agent in AZO targets, co-matching with doped wollastonite and kaolin modifiers, the problem of difficulty in coordinating the strength and density of AZO targets is solved, and the stability of high alkali resistance is significantly improved, achieving coordinated improvement of performance.

CN119569442APending Publication Date: 2025-03-07ZHUZHOU TORCH ANTAI NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411781201.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The strength and density performance of existing AZO targets are difficult to coordinately improve, and the stability performance of high alkali resistance is poor, which limits the efficiency of the product.

Method used

The matrix agent is used to combine wollastonite-doped blending agent and kaolin modifier. After molding and heat treatment, the strength and density performance of the AZO target body are improved and the stability of high alkali resistance is improved.

Benefits of technology

The strength, density and high alkali resistance stability of the AZO target blank have been significantly improved, and the overall performance of the product has been coordinated and improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172823450000111
    Figure BDA0005172823450000111
Patent Text Reader

Abstract

The modification method for improving the strength of the AZO target material green body comprises the following steps: uniformly blending 35-40 parts of zinc oxide, 5-10 parts of aluminum oxide, 2-4 parts of polyethylene glycol, 1-3 parts of sodium carboxymethyl cellulose and 20-30 parts of water to obtain a matrix agent; the preparation method comprises the following steps: uniformly blending 3-5 parts of a wollastonite-doped modifier and 2-4 parts of a kaolin modifier, adding the mixture into a matrix agent, and finally carrying out ball milling at a rotating speed of 1000r / min for 1 hour to obtain a ball-milled material. The AZO target material green body can be obtained by blending and coordinating the matrix agent with the wollastonite-doped blending agent and the kaolin modifier and carrying out molding and heat treatment, and the strength and compactness performance of the prepared AZO target material green body are harmoniously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of target materials, and in particular to a modification method for improving the strength of an AZO target material blank. Background Art

[0002] It has been widely used in thin-film solar cells. The raw materials Zn and Al used in AZO are abundant, easy to manufacture, low in cost, non-toxic, and have good thermal stability. Therefore, people are increasingly interested in the research of AZO (Al-dopedin Zinc Oxide) films. In recent years, AZO has further become a hot spot in TCO film research.

[0003] The strength and density of the AZO target material used in the prior art are difficult to improve in a coordinated manner, and the product has poor high alkali resistance and stability, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a modification method for improving the strength of AZO target blank, so as to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a modification method for improving the strength of an AZO target blank, comprising the following steps:

[0006] Step 1: 35-40 parts of zinc oxide, 5-10 parts of aluminum oxide, 2-4 parts of polyethylene glycol, 1-3 parts of sodium carboxymethyl cellulose and 20-30 parts of water are uniformly mixed to obtain a base agent;

[0007] Step 2: 3-5 parts of wollastonite-doped adjusting agent and 2-4 parts of kaolin modifier are mixed and evenly added into the base agent, and finally ball-milled at a speed of 1000 r / min for 1 hour to obtain a ball-milled material;

[0008] Step 3: Place the ball abrasive into a mold for molding, with a molding pressure of 20-30 MPa and a molding time of 20 min to obtain a molded body;

[0009] Step 4: Treat the formed body at 1250-1300°C for 2 hours. The treatment is completed.

[0010] Preferably, the preparation method of the wollastonite-doped adjusting agent is:

[0011] S01: irradiate the wollastonite in a proton irradiation box for 10-15 minutes at an irradiation power of 300W, and then preheat at 65°C for 1 hour to obtain preheated wollastonite;

[0012] S02: 5-8 parts of preheated wollastonite, 1-3 parts of lanthanum chloride solution and 3-5 parts of flaky talc are blended and added to 5-9 parts of sodium dodecylbenzene sulfonate solution to obtain wollastonite doping solution;

[0013] S03: immersing the nano-silicon dioxide into a 5% sodium citrate solution having a mass fraction of 3-5 times the total amount of the nano-silicon dioxide to obtain a nano-silicon dioxide liquid;

[0014] The nano-silicon dioxide liquid and the wollastonite doping liquid were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a wollastonite-doped adjusting agent.

[0015] Preferably, the mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-4%.

[0016] Preferably, the immersion stirring speed for full immersion is 550-650 r / min, and the immersion time is 20-30 min.

[0017] Preferably, the preparation method of the kaolin modifier is:

[0018] S101: subjecting kaolin to thermal modification treatment, and obtaining a thermally modified kaolin agent after the treatment is completed;

[0019] S102: The heat-modified kaolin agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin modifying agent.

[0020] Preferably, the specific operation steps of the thermal improvement treatment are:

[0021] First, heat to 160-170°C at a rate of 3-5°C / min, keep warm for 5-10 minutes, then heat to 230-240°C at a rate of 2-3°C / min, keep warm for 5 minutes, and finally air cool to room temperature.

[0022] Preferably, the stirring speed of the stirring modification treatment is 350-400 r / min, and the stirring time is 20-30 min.

[0023] Preferably, the preparation method of the modified liquid is:

[0024] 1-3 parts of silane coupling agent and 2-5 parts of cobalt nitrate solution are added to 5-8 parts of sodium alginate solution, and then 2-4 parts of yttrium oxide and 1-2 parts of stearic acid are added, and stirred thoroughly to obtain a modified solution.

[0025] Preferably, the mass fraction of the cobalt nitrate solution is 2-5%; the mass fraction of the sodium alginate solution is 3-6%.

[0026] Preferably, the silane coupling agent is silane coupling agent KH560.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The AZO target material blank of the present invention is prepared by blending and coordinating a matrix agent with a wollastonite-doped adjusting agent and a kaolin modifier, and the obtained AZO target material blank is formed and heat treated, and the strength and density of the prepared AZO target material blank are coordinated and improved, and the high alkali resistance and stability performance of the product are remarkable; the adjusting agent doped with wollastonite takes wollastonite as a matrix and has a needle-shaped reinforcing effect, and is blended with a lanthanum chloride solution, a flaky talcum powder and a sodium dodecylbenzene sulfonate solution, and then coordinating with a nano-silicon dioxide liquid, and the adjusting agent doped with wollastonite obtained by blending and coordinating the raw materials and coordinating the raw materials strengthens the interface of the raw materials in the system, and optimizes the coordination of product performance; the kaolin is subjected to a heat improvement treatment, the interlayer spacing of the product is increased, and the kaolin modifier obtained by using a specific modifying liquid for improvement has an enhanced coordination effect with the adjusting agent doped with wollastonite, and the product performance is further improved. DETAILED DESCRIPTION

[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] A modification method for improving the strength of an AZO target blank in this embodiment includes the following steps:

[0031] Step 1: 35-40 parts of zinc oxide, 5-10 parts of aluminum oxide, 2-4 parts of polyethylene glycol, 1-3 parts of sodium carboxymethyl cellulose and 20-30 parts of water are uniformly mixed to obtain a base agent;

[0032] Step 2: 3-5 parts of wollastonite-doped adjusting agent and 2-4 parts of kaolin modifier are mixed and evenly added into the base agent, and finally ball-milled at a speed of 1000 r / min for 1 hour to obtain a ball-milled material;

[0033] Step 3: Place the ball abrasive into a mold for molding, with a molding pressure of 20-30 MPa and a molding time of 20 min to obtain a molded body;

[0034] Step 4: Treat the formed body at 1250-1300°C for 2 hours. The treatment is completed.

[0035] The preparation method of the wollastonite-doped adjusting agent of this embodiment is as follows:

[0036] S01: irradiate the wollastonite in a proton irradiation box for 10-15 minutes at an irradiation power of 300W, and then preheat at 65°C for 1 hour to obtain preheated wollastonite;

[0037] S02: 5-8 parts of preheated wollastonite, 1-3 parts of lanthanum chloride solution and 3-5 parts of flaky talc are blended and added to 5-9 parts of sodium dodecylbenzene sulfonate solution to obtain wollastonite doping solution;

[0038] S03: immersing the nano-silicon dioxide into a 5% sodium citrate solution having a mass fraction of 3-5 times the total amount of the nano-silicon dioxide to obtain a nano-silicon dioxide liquid;

[0039] The nano-silicon dioxide liquid and the wollastonite doping liquid were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a wollastonite-doped adjusting agent.

[0040] The mass fraction of the lanthanum chloride solution in this embodiment is 3-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-4%.

[0041] The immersion stirring speed for full immersion in this embodiment is 550-650r / min, and the immersion time is 20-30min.

[0042] The preparation method of the kaolin modifier of this embodiment is:

[0043] S101: subjecting kaolin to thermal modification treatment, and obtaining a thermally modified kaolin agent after the treatment is completed;

[0044] S102: The heat-modified kaolin agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin modifying agent.

[0045] The specific operation steps of the thermal improvement treatment of this embodiment are:

[0046] First, heat to 160-170°C at a rate of 3-5°C / min, keep warm for 5-10 minutes, then heat to 230-240°C at a rate of 2-3°C / min, keep warm for 5 minutes, and finally air cool to room temperature.

[0047] The stirring speed of the stirring modification treatment in this embodiment is 350-400 r / min, and the stirring time is 20-30 min.

[0048] The preparation method of the modified liquid of this embodiment is:

[0049] 1-3 parts of silane coupling agent and 2-5 parts of cobalt nitrate solution are added to 5-8 parts of sodium alginate solution, and then 2-4 parts of yttrium oxide and 1-2 parts of stearic acid are added, and stirred thoroughly to obtain a modified solution.

[0050] The mass fraction of the cobalt nitrate solution in this embodiment is 2-5%; the mass fraction of the sodium alginate solution is 3-6%.

[0051] The silane coupling agent of this embodiment is silane coupling agent KH560.

[0052] Example 1.

[0053] A modification method for improving the strength of an AZO target blank in this embodiment comprises the following steps:

[0054] Step 1: 35 parts of zinc oxide, 5 parts of aluminum oxide, 2 parts of polyethylene glycol, 1 part of sodium carboxymethyl cellulose and 20 parts of water are uniformly mixed to obtain a base agent;

[0055] Step 2: 3 parts of wollastonite-doped adjusting agent and 2 parts of kaolin modifier are mixed and evenly added into the base agent, and finally ball-milled at a speed of 1000 r / min for 1 hour to obtain a ball-milled material;

[0056] Step 3: Place the ball abrasive into a mold for molding, with a molding pressure of 20 MPa and a molding time of 20 min to obtain a molded body;

[0057] Step 4: Treat the formed body at 1250°C for 2 hours.

[0058] The preparation method of the wollastonite-doped adjusting agent of the present embodiment is as follows:

[0059] S01: irradiate wollastonite in a proton irradiation box for 10 minutes at an irradiation power of 300 W, and then preheat at 65° C. for 1 hour to obtain preheated wollastonite;

[0060] S02: 5 parts of preheated wollastonite, 1 part of lanthanum chloride solution and 3 parts of flaky talc are blended and added into 5 parts of sodium dodecylbenzene sulfonate solution to obtain wollastonite doping solution;

[0061] S03: immersing the nano-silicon dioxide into a 5% sodium citrate solution having a mass fraction of 3 times the total amount of the nano-silicon dioxide to obtain a nano-silicon dioxide liquid;

[0062] The nano-silicon dioxide liquid and the wollastonite doping liquid were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a wollastonite-doped adjusting agent.

[0063] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 2%.

[0064] The immersion stirring speed for full immersion in this embodiment is 550 r / min, and the immersion time is 20 min.

[0065] The preparation method of the kaolin modifier of this embodiment is:

[0066] S101: subjecting kaolin to thermal modification treatment, and obtaining a thermally modified kaolin agent after the treatment is completed;

[0067] S102: The heat-modified kaolin agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin modifying agent.

[0068] The specific operation steps of the thermal improvement treatment of this embodiment are:

[0069] First, heat to 160°C at a rate of 3°C / min, keep warm for 5 min, then heat to 230°C at a rate of 2°C / min, keep warm for 5 min, and finally air cool to room temperature.

[0070] The stirring speed of the stirring modification treatment in this embodiment is 350 r / min, and the stirring time is 20 min.

[0071] The preparation method of the modified liquid of this embodiment is:

[0072] 1 part of silane coupling agent and 2 parts of cobalt nitrate solution were added to 5 parts of sodium alginate solution, and then 2 parts of yttrium oxide and 1 part of stearic acid were added, and stirred thoroughly to obtain a modified solution.

[0073] The mass fraction of the cobalt nitrate solution in this embodiment is 2%; the mass fraction of the sodium alginate solution is 3%.

[0074] The silane coupling agent of this embodiment is silane coupling agent KH560.

[0075] Example 2.

[0076] A modification method for improving the strength of an AZO target blank in this embodiment includes the following steps:

[0077] Step 1: 40 parts of zinc oxide, 10 parts of aluminum oxide, 4 parts of polyethylene glycol, 3 parts of sodium carboxymethyl cellulose and 30 parts of water are uniformly mixed to obtain a base agent;

[0078] Step 2: 5 parts of wollastonite-doped adjusting agent and 4 parts of kaolin modifier are mixed and evenly added into the base agent, and finally ball-milled at a speed of 1000 r / min for 1 hour to obtain a ball-milled material;

[0079] Step 3: Place the ball abrasive into a mold for molding, with a molding pressure of 30 MPa and a molding time of 20 min to obtain a molded body;

[0080] Step 4: Treat the formed body at 1300°C for 2 hours. The treatment is completed.

[0081] The preparation method of the wollastonite-doped adjusting agent of this embodiment is as follows:

[0082] S01: irradiate the wollastonite in a proton irradiation box for 15 minutes at an irradiation power of 300 W, and then preheat at 65° C. for 1 hour to obtain preheated wollastonite;

[0083] S02: 8 parts of preheated wollastonite, 3 parts of lanthanum chloride solution and 5 parts of flaky talc are blended and added into 9 parts of sodium dodecylbenzene sulfonate solution to obtain wollastonite doping solution;

[0084] S03: immersing the nano-silicon dioxide into a 5% sodium citrate solution with a mass fraction of 5 times the total amount of the nano-silicon dioxide to obtain a nano-silicon dioxide liquid;

[0085] The nano-silicon dioxide liquid and the wollastonite doping liquid were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a wollastonite-doped adjusting agent.

[0086] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4%.

[0087] The immersion stirring speed for full immersion in this embodiment is 650 r / min, and the immersion time is 30 min.

[0088] The preparation method of the kaolin modifier of this embodiment is:

[0089] S101: subjecting kaolin to thermal modification treatment, and obtaining a thermally modified kaolin agent after the treatment is completed;

[0090] S102: The heat-modified kaolin agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin modifying agent.

[0091] The specific operation steps of the thermal improvement treatment of this embodiment are:

[0092] First, heat to 170°C at a rate of 5°C / min, keep warm for 10 min, then heat to 240°C at a rate of 3°C / min, keep warm for 5 min, and finally air cool to room temperature.

[0093] The stirring speed of the stirring modification treatment in this embodiment is 400 r / min, and the stirring time is 30 min.

[0094] The preparation method of the modified liquid of this embodiment is:

[0095] 3 parts of silane coupling agent and 5 parts of cobalt nitrate solution were added to 8 parts of sodium alginate solution, and then 4 parts of yttrium oxide and 2 parts of stearic acid were added, and stirred thoroughly to obtain a modified solution.

[0096] The mass fraction of the cobalt nitrate solution in this embodiment is 5%; the mass fraction of the sodium alginate solution is 6%.

[0097] The silane coupling agent of this embodiment is silane coupling agent KH560.

[0098] Example 3.

[0099] A modification method for improving the strength of an AZO target blank in this embodiment includes the following steps:

[0100] Step 1: 37.5 parts of zinc oxide, 7.5 parts of aluminum oxide, 3 parts of polyethylene glycol, 2 parts of sodium carboxymethyl cellulose and 25 parts of water are uniformly mixed to obtain a base agent;

[0101] Step 2: 4 parts of wollastonite-doped adjusting agent and 3 parts of kaolin modifier are mixed and evenly added into the base agent, and finally ball-milled at a speed of 1000 r / min for 1 hour to obtain a ball-milled material;

[0102] Step 3: Place the ball abrasive into a mold for molding, with a molding pressure of 25 MPa and a molding time of 20 min to obtain a molded body;

[0103] Step 4: Treat the formed body at 1275°C for 2 hours.

[0104] The preparation method of the wollastonite-doped adjusting agent of this embodiment is as follows:

[0105] S01: irradiate wollastonite in a proton irradiation box for 12 minutes at an irradiation power of 300 W, and then preheat at 65° C. for 1 hour to obtain preheated wollastonite;

[0106] S02: 6.5 parts of preheated wollastonite, 2 parts of lanthanum chloride solution and 4 parts of flaky talc are blended and added into 7 parts of sodium dodecylbenzene sulfonate solution to obtain wollastonite doping solution;

[0107] S03: immersing the nano-silicon dioxide into a 5% sodium citrate solution having a mass fraction of 4 times the total amount of the nano-silicon dioxide to obtain a nano-silicon dioxide liquid;

[0108] The nano-silicon dioxide liquid and the wollastonite doping liquid were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a wollastonite-doped adjusting agent.

[0109] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 3%.

[0110] The immersion stirring speed for full immersion in this embodiment is 600 r / min, and the immersion time is 25 min.

[0111] The preparation method of the kaolin modifier of this embodiment is:

[0112] S101: subjecting kaolin to thermal modification treatment, and obtaining a thermally modified kaolin agent after the treatment is completed;

[0113] S102: The heat-modified kaolin agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin modifying agent.

[0114] The specific operation steps of the thermal improvement treatment of this embodiment are:

[0115] First, the temperature was raised to 165°C at a rate of 4°C / min and kept at that temperature for 7.5 min. Then, the temperature was raised to 235°C at a rate of 2.5°C / min and kept at that temperature for 5 min. Finally, the mixture was air-cooled to room temperature.

[0116] The stirring speed of the stirring modification treatment in this embodiment is 370 r / min, and the stirring time is 25 min.

[0117] The preparation method of the modified liquid of this embodiment is:

[0118] 2 parts of silane coupling agent and 3.5 parts of cobalt nitrate solution were added to 6.5 parts of sodium alginate solution, and then 3 parts of yttrium oxide and 1.5 parts of stearic acid were added, and stirred thoroughly to obtain a modified solution.

[0119] The mass fraction of the cobalt nitrate solution in this embodiment is 3.5%; the mass fraction of the sodium alginate solution is 4.5%.

[0120] The silane coupling agent of this embodiment is silane coupling agent KH560.

[0121] Example 4.

[0122] A modification method for improving the strength of an AZO target blank in this embodiment comprises the following steps:

[0123] Step 1: 36 parts of zinc oxide, 6 parts of aluminum oxide, 3 parts of polyethylene glycol, 2 parts of sodium carboxymethyl cellulose and 22 parts of water are uniformly mixed to obtain a base agent;

[0124] Step 2: 4 parts of wollastonite-doped adjusting agent and 3 parts of kaolin modifier are mixed and evenly added into the base agent, and finally ball-milled at a speed of 1000 r / min for 1 hour to obtain ball-milled material;

[0125] Step 3: Place the ball abrasive into a mold for molding, with a molding pressure of 22 MPa and a molding time of 20 min to obtain a molded body;

[0126] Step 4: Treat the formed body at 1260°C for 2 hours until the treatment is completed.

[0127] The preparation method of the wollastonite-doped adjusting agent of the present embodiment is as follows:

[0128] S01: irradiate wollastonite in a proton irradiation box for 12 minutes at an irradiation power of 300 W, and then preheat at 65° C. for 1 hour to obtain preheated wollastonite;

[0129] S02: 6 parts of preheated wollastonite, 2 parts of lanthanum chloride solution and 4 parts of flaky talc are blended and added into 6 parts of sodium dodecylbenzene sulfonate solution to obtain wollastonite doping solution;

[0130] S03: immersing the nano-silicon dioxide into a 5% sodium citrate solution having a mass fraction of 4 times the total amount of the nano-silicon dioxide to obtain a nano-silicon dioxide liquid;

[0131] The nano-silicon dioxide liquid and the wollastonite doping liquid were mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a wollastonite-doped adjusting agent.

[0132] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 3%.

[0133] The immersion stirring speed for full immersion in this embodiment is 570 r / min, and the immersion time is 22 min.

[0134] The preparation method of the kaolin modifier of this embodiment is:

[0135] S101: subjecting kaolin to thermal modification treatment, and obtaining a thermally modified kaolin agent after the treatment is completed;

[0136] S102: The heat-modified kaolin agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin modifying agent.

[0137] The specific operation steps of the thermal improvement treatment of this embodiment are:

[0138] The temperature was first raised to 162°C at a rate of 4°C / min and kept at that temperature for 6 min. The temperature was then raised to 235°C at a rate of 2°C / min and kept at that temperature for 5 min. Finally, the mixture was air-cooled to room temperature.

[0139] The stirring speed of the stirring modification treatment in this embodiment is 360 r / min, and the stirring time is 22 min.

[0140] The preparation method of the modified liquid of this embodiment is:

[0141] 2 parts of silane coupling agent and 3 parts of cobalt nitrate solution were added to 6 parts of sodium alginate solution, and then 3 parts of yttrium oxide and 1 part of stearic acid were added, and stirred thoroughly to obtain a modified solution.

[0142] The mass fraction of the cobalt nitrate solution in this embodiment is 3%; the mass fraction of the sodium alginate solution is 4%.

[0143] The silane coupling agent of this embodiment is silane coupling agent KH560.

[0144] Comparative Example 1.

[0145] The difference from Example 3 is that no adjusting agent for doping wollastonite is added.

[0146] Comparative Example 2.

[0147] The difference from Example 3 is that no nano-silicon dioxide liquid is added in the preparation of the wollastonite-doped adjusting agent.

[0148] Comparative Example 3.

[0149] The difference from Example 3 is that no wollastonite doping liquid is added in the preparation of the wollastonite-doped adjusting agent.

[0150] Comparative Example 4.

[0151] The difference from Example 3 is that no lanthanum chloride solution and flaky talc powder are added to the wollastonite doping solution.

[0152] Comparative Example 5.

[0153] The difference from Example 3 is that no kaolin modifier is added.

[0154] Comparative Example 6.

[0155] The difference from Example 3 is that no modifying liquid is added in the preparation of the kaolin modifier.

[0156] Comparative Example 7.

[0157] The difference from Example 3 is that no cobalt nitrate solution and yttrium oxide are added to the modified solution.

[0158] The product performances of Examples 1-4 and Comparative Examples 1-7 of the present invention were tested under conventional conditions, and placed in 5% sodium hydroxide alkaline mist conditions for 24 hours to test the alkali corrosion resistance of the products. The test results are as follows.

[0159]

[0160] It can be seen from Examples 1-4 and Comparative Examples 1-7 that the products of Examples 1-4 of the present invention have excellent tensile strength, excellent product density effect, and excellent product performance stability under alkaline corrosion conditions;

[0161] The present invention does not add one of the wollastonite-doped adjusting agent and the kaolin modifier, and the performance effect of the product is significantly deteriorated. The two are used in combination to achieve synergistic effects, and the product performance effect is most obvious;

[0162] When no nano-silicon dioxide liquid is added in the preparation of the wollastonite-doped adjusting agent, no wollastonite doping liquid is added in the preparation of the wollastonite-doping adjusting agent, no lanthanum chloride solution and flaky talcum powder are added to the wollastonite doping liquid, no modifying liquid is added in the preparation of the kaolin modifier, and no cobalt nitrate solution and yttrium oxide are added to the modifying liquid, the performance of the products tends to deteriorate, and other methods are not as obvious as the effect of the present invention. The wollastonite doping liquid prepared by the specific method of the present invention has the most significant product performance effect.

[0163] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0164] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A modification method for improving the strength of an AZO target blank, characterized in that: The following steps are involved: Step 1: 35-40 parts of zinc oxide, 5-10 parts of aluminum oxide, 2-4 parts of polyethylene glycol, 1-3 parts of sodium carboxymethyl cellulose and 20-30 parts of water are uniformly mixed to obtain a base agent; Step 2: 3-5 parts of wollastonite-doped adjusting agent and 2-4 parts of kaolin modifier are mixed and evenly added into the base agent, and finally ball-milled at a speed of 1000 r / min for 1 hour to obtain a ball-milled material; Step 3: Place the ball abrasive into a mold for molding, with a molding pressure of 20-30 MPa and a molding time of 20 min to obtain a molded body; Step 4: Treat the formed body at 1250-1300°C for 2 hours. The treatment is completed.

2. A modification method for improving the strength of an AZO target blank according to claim 1, characterized in that: The preparation method of the wollastonite-doped adjusting agent is as follows: S01: irradiate the wollastonite in a proton irradiation box for 10-15 minutes at an irradiation power of 300W, and then preheat at 65°C for 1 hour to obtain preheated wollastonite; S02: 5-8 parts of preheated wollastonite, 1-3 parts of lanthanum chloride solution and 3-5 parts of flaky talc are blended and added to 5-9 parts of sodium dodecylbenzene sulfonate solution to obtain wollastonite doping solution; S03: immersing the nano-silicon dioxide into a 5% sodium citrate solution having a mass fraction of 3-5 times the total amount of the nano-silicon dioxide to obtain a nano-silicon dioxide liquid; The nano-silicon dioxide liquid and the wollastonite doping liquid were mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain a wollastonite-doped adjusting agent.

3. A modification method for improving the strength of an AZO target blank according to claim 2, characterized in that: The mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-4%.

4. A modification method for improving the strength of an AZO target blank according to claim 2, characterized in that: The stirring speed of the immersion for full immersion is 550-650 r / min, and the immersion time is 20-30 min.

5. A modification method for improving the strength of an AZO target blank according to claim 1, characterized in that: The preparation method of the kaolin modifier is: S101: subjecting kaolin to thermal modification treatment, and obtaining a thermally modified kaolin agent after the treatment is completed; S102: The heat-modified kaolin agent and the modifying liquid are stirred and modified in a weight ratio of 2:

5. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin modifying agent.

6. A modification method for improving the strength of an AZO target blank according to claim 5, characterized in that: The specific operation steps of the thermal improvement treatment are: First, heat to 160-170°C at a rate of 3-5°C / min, keep warm for 5-10 minutes, then heat to 230-240°C at a rate of 2-3°C / min, keep warm for 5 minutes, and finally air cool to room temperature.

7. A modification method for improving the strength of an AZO target blank according to claim 5, characterized in that: The stirring speed of the stirring modification treatment is 350-400 r / min, and the stirring time is 20-30 min.

8. A modification method for improving the strength of an AZO target blank according to claim 5, characterized in that: The preparation method of the modified liquid is: 1-3 parts of silane coupling agent and 2-5 parts of cobalt nitrate solution are added to 5-8 parts of sodium alginate solution, and then 2-4 parts of yttrium oxide and 1-2 parts of stearic acid are added, and stirred thoroughly to obtain a modified solution.

9. A modification method for improving the strength of an AZO target blank according to claim 8, characterized in that: The mass fraction of the cobalt nitrate solution is 2-5%; the mass fraction of the sodium alginate solution is 3-6%.

10. A modification method for improving the strength of an AZO target blank according to claim 8, characterized in that: The silane coupling agent is silane coupling agent KH560.

Citation Information

Cited By

  • Special aluminum alloy power cable for railway and preparation method thereof

    CN120137491A